Inclusive Education for Religious Minorities: The Syriacs in Turkey - Halis Sakız; Abdurrahman Ekinci; Güldest Baş (Social Inclusion, 2020)
Expanding the scope of inclusion beyond specific groups such as individuals with disabilities has led to the investigation of school systems’ inclusiveness from the perspective of all students. With this in mind, this research investigated the experiences of students and parents belonging to the ancient Syriac community in Turkey, who inhabited Mesopotamia since the inception of Christianity. Obtaining the views of 43 parents and their 46 children through semi-structured interviews, the school system was investigated at a political, cultural, and practical level in terms of the educational inclusion of Syriac individuals. Overall, student and parent views indicated that: (a) policy-making lacked an approach to reach all students and organize support for diversity; (b) school cultures needed to build a community whereby inclusive values were established; and (c) school practices lacked the organization to target and ensure the learning of all and mobilize resources to achieve this aim. Details of findings are included and discussed. Implications address the importance of building schools that consider the increasingly diverse school populations around the world, with a particular focus on cultural and religious diversity.